Detecting cavitation in mercury exposed to a high-energy pulsed proton beam - Manzi, N; Chitnis, P; Holt, R; Roy, R; Cleveland, R; Riemer, B; Wendel, M (Acoustical Society of America, 2010)
The Oak Ridge National Laboratory Spallation Neutron Source employs a high-energy pulsed proton beam incident on a mercury target to generate short bursts of neutrons. Absorption of the proton beam produces rapid heating of the mercury, resulting in the formation of acoustic shock waves and the nucleation of cavitation bubbles. The subsequent collapse of these cavitation bubbles promote erosion of the steel target walls. Preliminary measurements using two passive cavitation detectors (megahertz-frequency focused and unfocused piezoelectric transducers) installed in a mercury test target to monitor cavitation generated by proton beams with charges ranging from 0.041 to 4.1 muC will be reported on. Cavitation was initially detected for a beam charge of 0.082 muC by the presence of an acoustic emission approximately 250 mus after arrival of the incident proton beam. This emission was consistent with an inertial cavitation collapse of a bubble with an estimated maximum bubble radius of 0.19 mm, based on collapse time. The peak pressure in the mercury for the initiation of cavitation was predicted to be 0.6 MPa. For a beam charge of 0.41 muC and higher, the lifetimes of the bubbles exceeded the reverberation time of the chamber ( approximately 300 mus), and distinct windows of cavitation activity were detected, a phenomenon that likely resulted from the interaction of the reverberation in the chamber and the cavitation bubbles.